Five new species of the family Trischistomatidae (Nematoda: Enoplida) from North and Central America, with keys to the species of Trischistoma and Tripylina - Prado-Vera, Ignacio Cid Del; Ferris, Howard; Nadler, Steven A. (Zootaxa, 2016)
Three new species of Trischistoma and two new species of Tripylina (Trischistomatidae) are described. Trischistoma ripariana n. sp. was collected in the surface organic material and upper rhizosphere soil on a stream bank in Oakville, California, USA. It is characterized by a short, thin body, the vulva at 79–83%, a small index c (17–29) and a short tail, 34–57 µm. Trischistoma corticulensis n. sp. was found in moss on tree bark in a tropical forest at the La Mancha Ecological Institute, Veracruz State, México. The vulva is at 67–73% and the tail is elongate conoid (51–84 µm). Trischistoma helicoformis n. sp. was collected on lichen growing on tree bark near the Carretera Interamericana in Costa Rica. It is characterized by its spiral shape after fixation, the tail length (76–101 µm), a very small index c (10–14.5) and very small sclerotised pieces around the vagina. Tripylina rorkabanarum n. sp. was collected from moss on tree bark in a tropical forest at the La Mancha Ecological Institute. It is characterized by the presence of two cervical setae, the position of the subventral teeth posterior to the dorsal tooth, the absence of sclerotized pieces around the vagina and the distance of the dorsal tooth from the anterior, 10–15 μm. Tripylina iandrassyi n. sp. was collected from soil around a banana tree at the La Mancha Ecological Institute. It is characterized by the presence of a post-uterine sac, well-developed buccal lips, subventral teeth located posterior to the dorsal tooth, one cervical seta in females and two in males, and by spicules not completely surrounded by a muscular sheath.